Pengaruh Inovasi Dan Kreatifitas Terhadap Kinerja Usaha Pelaku Umkm Jajanan Pasar Di Kecamatan Tuah Madani Kota Pekanbaru - Sukriani, Nurul; Febrina, Dian (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This study aims to analyze the influence of Knowledge, Ability, and Skills on the Business Performance of MSME (Micro, Small, and Medium Enterprises) traditional snack vendors in Tuah Madani District, Pekanbaru City. The data analysis method used is quantitative. Data sources include both primary and secondary data, collected through questionnaires and interviews. The population in this study consists of MSME actors engaged in traditional snack businesses in Tuah Madani District, Pekanbaru City. Since the exact number of the population is unknown, the Wibisono formula was used to determine the sample size, resulting in a total of 97 respondents. The research findings indicate a significant simultaneous influence of Knowledge, Ability, and Skills on the Business Performance of MSME traditional snack vendors in Tuah Madani District, Pekanbaru City. Partially, Knowledge, Ability, and Skills were also found to have a significant influence on business performance.